2017
DOI: 10.18632/oncotarget.17396
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PKM2 and GLS1 expression can significantly reverse oxaliplatin-resistance in colorectal cancer cells

Abstract: Clinical treatment for colorectal cancer (CRC) thus far encounters a huge challenge due to oxaliplatin-resistance. As crucial rate-limiting enzymes in aerobic glycolysis and glutaminolysis, pyruvate kinase M2 type (PKM2) and kidney-type glutaminase (GLS1) are proposed to carry important implications in colorectal carcinogenesis and drug-resistance. This study aimed to explore the possible association of oxaliplatin-resistance with aerobic glycolysis/glutaminolysis indexed by PKM2/GLS1 expression. PKM2 and GLS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Indeed, there are several in vitro studies that demonstrate the interference of aerobic glycolysis and of PKM2 on platinum-sensitivity by modification of oxidative phosphorylation rate, by alteration of lactate production, and by restriction of drug oxidative role. For instance, knockdown of PKM2 expression in colorectal and bladder cancer cells re-boost platinum sensitivity and induce cell apoptosis [33,34]. Another recent study performed in ovarian cancer cell lines showed the overexpression of PKM2 that in turn increased CCND1 expression, whereas it decreased CDKN1A expression; determinants involved in the increase of proliferation and in the decrease of apoptosis of ovarian cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are several in vitro studies that demonstrate the interference of aerobic glycolysis and of PKM2 on platinum-sensitivity by modification of oxidative phosphorylation rate, by alteration of lactate production, and by restriction of drug oxidative role. For instance, knockdown of PKM2 expression in colorectal and bladder cancer cells re-boost platinum sensitivity and induce cell apoptosis [33,34]. Another recent study performed in ovarian cancer cell lines showed the overexpression of PKM2 that in turn increased CCND1 expression, whereas it decreased CDKN1A expression; determinants involved in the increase of proliferation and in the decrease of apoptosis of ovarian cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that the PKM2 overexpression is associated with chemoresistance in various cancers 59 , 60 , the PAK2–c-Myc–PKM2 axis might be responsible for chemoresistance in HNC. Interestingly, we observed that PAK2 depletion reduced chemotherapeutic resistance in HNC cells, which further correlates with poor survival of HNC patients with higher expression of PAK2.…”
Section: Discussionmentioning
confidence: 99%
“…miR-122 targets PKM2 in the colon cancer cells, and forced expression of miR-122 re-sensitizes 5-fluorouracil (5-FU)-resistant cells to 5-FU by inhibiting PKM2 [ 43 ]. Silencing PKM2 and kidney-type glutaminase expression significantly reverses the resistance of colorectal cancer cells to oxaliplatin [ 46 ]. Inhibition of PKM2 in esophageal squamous cell carcinoma cells significantly decreases cisplatin resistance and increases apoptosis by inactivating the pentose phosphate pathway [ 47 ].…”
Section: Roles Of Pkm2 In Cancermentioning
confidence: 99%